Federal grants and contracts for unclassified research in the life sciences. - National Science Foundation (U.S.) (National Science Foundation., 1952)
Issue for Fiscal year 1954 accompanied by separately published section with title: Projects listed by agencies.
Issue for Fiscal year 1954 accompanied by separately published section with title: Projects listed by agencies.
Latest issue consulted: 1958
Available online through HathiTrust Emergency Access Service. Click the HathiTrust button on the right and log in to access this book online
Keywords: Research Support as Topic. / (DNLM)D012109; Medicine. / (DNLM)D008511; Government Agencies. / (DNLM)D006077; Biology. / (DNLM)D001695; Biology / Research grants. / fast / (OCoLC)fst00832466; Biology / Research grants / United States / Directories.; United States. / (DNLM)D014481; United States. / fast / (OCoLC)fst01204155; Directory. / (DNLM)D016435; Directories. / fast / (OCoLC)fst01423796